Measurement of Writing Skills in Observation Reports by Boarding and Non-boarding Students in Grade VIII - Ernita Putri Andini; Memet Sudaryanto; Vera Krisnawati (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Indonesian Language learning at the junior high school level covers various language skills, one of which is writing. Theability to write observational report text is one of the important materials taught in grade VIII. This ability still shows differences in student learning outcomes in different learning environments. The purpose of this study was to determine the differences in the ability to write observational report texts between boarding and nonboarding students of grade VIII junior high schools in Purwokerto. This study used a quantitative approach with a comparative study design. The study population was all grade VIII junior high school students in Purwokerto with a purposive sampling technique totaling 100 students. 50 students of Muhammadiyah Boarding School Zam Zam as a boarding school and 50 students of SMP Negeri 4 Purwokerto as a nonboarding school. The data collection instrument was a valid and reliable assessment rubric. The data collection process was carried out through a performance test for writing observational report texts using LKPD containing instructions. Data analysis used descriptive statistics and independent sample t-test. The results showed that the average score of the ability to write observational report texts for boarding students was higher than for nonboarding students. The results of the independent sample t-test also showed a significant difference in the ability to write observational reports between boarding and nonboarding students. This study demonstrates that differences in learning environments can impact students writing skills. Teachers can utilize these findings to develop more effective writing learning strategies tailored to their students learning environments.